Le Rythme grec d'Héraclite à Aristote - Sauvanet, Pierre (Paris Presses Universitaires de France, 1999)
We are most familiar with Plato's definition of Greek rhythm: the order of movement, i.e. the order manifested by the moving body in dance. We often overlook the fact that the term rhythm, in its various linguistic guises, runs through the whole of Greek philosophy, and that it does not just have the musical meaning we know. For Democritus, it was an original concept used to designate the shape of moving atoms, and for certain sophists, it characterised material nature. With Plato and Arisotle, rhythm definitively took on its musical and poetic meaning. Systematic recourse to the texts shows that the term rhythm first characterised ‘form or figure in their relation to time’. It could be said that Greek rhythm is special in that it lies at the crossroads of space and time, order and movement, and is in a sense a ‘temporalised spatial form’. But what is rhuthmos? The author's hypothesis is that rhuthmos, derived from the verb rheo (to flow), is philosophically linked to the panta rhei, everything flows. In this hypothesis, which remains to be developed in this essay, rhuthmos clearly becomes an issue in the philosophical debate of ancient Greece. (Translated with DeepL.com)
Keywords: Classical Antiquity (8th Century BC-6th Century AD); Rhythm; Philosophy